Dialogues in the Philosophy of Religion - Hick, J. author. aut Link
XV, 217 p. 1 illus.
Keywords: This is a collection of John Hick's essays on the understanding of the world's religions as different human responses to the same ultimate transcendent reality. He is in dialogue with contemporary philosophers (some of whom contribute new responses); with Evangelicals; with the Vatican and other both Catholic and Protestant theologians.